Finite-time stability results for fractional damped dynamical systems with time delays - Arthi, Ganesan; Brindha, Nallasamy; Baleanu, Dumitru (Nonlinear Analysis: Modelling and Control, 2022)
This paper is explored with the stability procedure for linear nonautonomous multiterm fractional damped systems involving time delay. Finite-time stability (FTS) criteria have been developed based on the extended form of Gronwall inequality. Also, the result is deduced to a linear autonomous case. Two examples of applications of stability analysis in numerical formulation are described showing the expertise of theoretical prediction.
Keywords: damped system; fractional order; finite-time stability; time delay